Artificial Intelligence Applications in Information and Communication Technologies - Laalaoui, Yacine; Bouguila, Nizar (Studies in Computational Intelligence, 2015)
This book presents various recent applications of Artificial Intelligence in Information and Communication Technologies such as Search and Optimization methods, Machine Learning, Data Representation and Ontologies, and Multi-agent Systems. The main aim of this book is to help Information and Communication Technologies (ICT) practitioners in managing efficiently their platforms using AI tools and methods and to provide them with sufficient Artificial Intelligence background to deal with real-life problems.  .